Readiness of Faculty and Staff for Alternative Work Arrangements: Implications for a Hybrid Workforce Model - Mendoza, Kristin Joy A.; Asio, John Mark R.; Abarintos, Erlinda C.; Paguio, Darwin P. (Future Science / FSH-PH Publications, 2022)
The Pandemic thrust the workforce in the private and public sectors into alternative work arrangements. For higher education institutions in the Philippines, it was a sudden shift to a flexible learning modality to ensure continuity of learning. This cross-sectional descriptive study assessed the readiness of 219 faculty and 69 staff in a local college for alternative work arrangements in terms of access to transportation, their health condition, information technology resources, connectivity, and their preferences in terms of alternative work arrangements. Results show that most respondents use public transportation to work and a minor percentage have medical conditions that make them susceptible to the COVID-19 virus. The top information technology (I.T) resources available to the respondents at home are smartphones/iPhones, laptops, and printers. Most have intermittent internet connectivity, with DSL/Fiber Connectivity and mobile data the most common types. Finally, the majority believe they can work from home, given the nature of their duties. However, more respondents prefer a hybrid work arrangement to a full-time work-from-home placement. The researchers presented some essential implications for a hybrid workforce model at the end of the paper.